2010
DOI: 10.26522/ssj.v3i2.1015
|View full text |Cite
|
Sign up to set email alerts
|

Job Quality and Gender Inequality: Key Changes in Québec over the Last Decade

Abstract: Using a new typology based on information available from the Labour Force Survey, the authors analyse how job quality evolved in Québec for both women and men over the last decade (1997-2007). Results show that family situation and educational attainment are two important factors in the determination of gender inequality in the labour market. The analysis emphasizes the very significant decline in gender differences with regard to job quality (from 23% to 35% according to groups), especially for persons withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…We suggest, however, that this notion is perhaps too simplistic and possibly misleading. Considering there is evidence that suggests that the individuals opting for underemployment to minimize their WFC tend to be predominantly female (Cloutier, Bernard, & Tremblay, 2009; Trappe & Rosenfeld, 2000), this (potentially) erroneous stance could have far‐reaching implications.…”
mentioning
confidence: 99%
“…We suggest, however, that this notion is perhaps too simplistic and possibly misleading. Considering there is evidence that suggests that the individuals opting for underemployment to minimize their WFC tend to be predominantly female (Cloutier, Bernard, & Tremblay, 2009; Trappe & Rosenfeld, 2000), this (potentially) erroneous stance could have far‐reaching implications.…”
mentioning
confidence: 99%
“…In countries where breadwinner norms are still predominant, the association between job insecurity and health may be comparatively lower for women compared to men, as these are expected to contribute the most to the household income. In addition, the non-economic gender approach, which attributes inequalities to patriarchy and gender stereotypes within institutions and interactional contexts, could explain the low or negligible effects of insecurity as a stressor among women (Wang et al, 2008 ; Cloutier et al, 2009 ; Stier and Yaish, 2014 ). On the other hand, within a more gender-egalitarian culture, the negative effects of perceived job insecurity may be significant for women as much as for men (Kachi et al, 2018 ).…”
Section: Literature Review and Research Propositionsmentioning
confidence: 99%
“…Beyond the European context, Cloutier et al (2009) showed a narrowing of the gender gap in job quality in Quebec (Canada). This reduction of gender differences was particularly significant among childless employees and people with higher educational levels.…”
Section: Gender and Job Quality During The Economic Boommentioning
confidence: 99%